Vascular Endothelium in Neonatal Sepsis: Basic Mechanisms and Translational Opportunities - Pietrasanta, Carlo; Pugni, Lorenza; Ronchi, Andrea; Bottino, Ilaria; Ghirardi, Beatrice; Sanchez-Schmitz, Guzman; Borriello, Francesco; Mosca, Fabio; Levy, Ofer (Frontiers in Pediatrics, 2019)
Neonatal sepsis remains a major health issue worldwide, especially for low-birth weight and premature infants, with a high risk of death and devastating sequelae. Apart from antibiotics and supportive care, there is an unmet need for adjunctive treatments to improve the outcomes of neonatal sepsis. Strong and long-standing research on adult patients has shown that vascular endothelium is a key player in the pathophysiology of sepsis and sepsis-associated organ failure, through a direct interaction with pathogens, leukocytes, platelets, and the effect of soluble circulating mediators, in part produced by endothelial cells themselves. Despite abundant evidence that the neonatal immune response to sepsis is distinct from that of adults, comparable knowledge on neonatal vascular endothelium is much more limited. Neonatal endothelial cells express lower amounts of adhesion molecules compared to adult ones, and present a reduced capacity to neutralize reactive oxygen species. Conversely, available evidence on biomarkers of endothelial damage in neonates is not as robust as in adult patients, and endothelium-targeted therapeutic opportunities for neonatal sepsis are almost unexplored. Here, we summarize current knowledge on the structure of neonatal vascular endothelium, its interactions with neonatal immune system and possible endothelium-targeted diagnostic and therapeutic tools for neonatal sepsis. Furthermore, we outline areas of basic and translational research worthy of further study, to shed light on the role of vascular endothelium in the context of neonatal sepsis.